2011
DOI: 10.1021/nn201601m
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Lithography on Monolayer Graphene Using Hydrogenation and Oxidation

Abstract: Monolayer graphene is one of the most interesting materials applicable to next-generation electronic devices due to its transport properties. However, realization of graphene devices requires suitable nanoscale lithography as well as a method to open a band gap in monolayer graphene. Nanoscale hydrogenation and oxidation are promising methods to open an energy band gap by modification of surface structures and to fabricate nanostructures such as graphene nanoribbons (GNRs). Until now it has been difficult to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
134
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(140 citation statements)
references
References 34 publications
2
134
0
3
Order By: Relevance
“…The most-studied chemically modified 2D material is oxidized graphene. Several works of different groups have demonstrated that friction in graphene is notably enhanced by oxidation [65][66][67]. For this reason, oxidized graphene can easily be distinguished from a graphite surface by lateral-force microscopy [67].…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The most-studied chemically modified 2D material is oxidized graphene. Several works of different groups have demonstrated that friction in graphene is notably enhanced by oxidation [65][66][67]. For this reason, oxidized graphene can easily be distinguished from a graphite surface by lateral-force microscopy [67].…”
Section: Figmentioning
confidence: 99%
“…During tip retraction, lifting these topmost layers leads to greater deformability of the surface, and thus increases the friction force. For hydrogenated graphene, the friction force is three times higher than for pristine graphene [65]. However, based on in situ cleaning with an AFM tip, Fessler et al attributed this to surface contamination [71].…”
Section: Figmentioning
confidence: 99%
“…Chemically modifying graphene markedly alters its optical 15 , electronic 16 and lubricating 17,18 properties. It should be noted that while prior work has shown that scanning probes can remove functional groups by locally applying heat 16,19 or electronic potential 20 ; mechanochemical cleavage by a scanning probe has not been addressed.…”
mentioning
confidence: 99%
“…Local AFM-tip-induced electrochemical reduction processes were used to pattern conductive pathways on insulating graphene oxide to fabricate micropatterned graphene field-effect transistors featuring high charge-carrier mobilities (Figure 4d,e) [92,93]. By changing the polarity of the applied voltage between graphene and a conductive AFM tip, hydrogenation and oxidation could be controlled at the nanoscale, and used to fabricate nanostructures such as graphene nanoribbons [94]. Changes due to the electro-reduction process could be monitored directly on a device by KPFM even at single sheet level [95].…”
Section: Electrical Modesmentioning
confidence: 99%